Knowledge of breast cancer and breast self-examination practice among Iranian women in Hamedan, Iran - Akhtari-Zavare, Mehrnoosh; Ghanbari-Baghestan, Abbas; Abd Latiff, Latiffah; Matinnia, Nasrin; Hoseini, Mozhgan (Asian Pacific Education Press, 2014)
BACKGROUND: In Iran, breast cancer is the most prevalent cancer in women and a major public health problem. METHODS: A cross sectional study was carried out to determine knowledge on breast cancer and breast self- examination (BSE) practices of 384 females living in the city of Hamadan, Iran. A purposive sampling method was adopted and data were collected via face-to-face interviews based on a validated questionnaire developed for this study. RESULTS: Among respondents 268 (69.8%) were married and 144 (37.5%) of the respondents reported having a family history of breast cancer. One hundred respondents (26.0%) claimed they practiced BSE. Level of breast cancer knowledge was significantly associated with BSE practice (p=0.000). There was no association with demographic details (p<0.05). CONCLUSION: The findings showed that Iranian women's knowledge regarding breast cancer and the practice of BSE is inadequate. Targeted education should be implemented to improve early detection of breast cancer.